2003
DOI: 10.1093/gerona/58.2.b108
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Resistance-Training-Induced Myofiber Hypertrophy Among Older Adults

Abstract: We tested the hypothesis that older men (n = 9, 69 +/- 2 years) would experience greater resistance-training-induced myofiber hypertrophy than older women (n = 5, 66 +/- 1 years) following knee extensor training 3 days per week at 65-80% of one-repetition maximum for 26 weeks. Vastus lateralis biopsies were analyzed for myofiber areas, myosin heavy chain isoform distribution, and levels of mRNA for insulin-like growth factor 1 (IGF-1), IGFR1, and myogenin. Gender x Training interactions (p <.05) indicate great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
5
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 67 publications
13
111
5
6
Order By: Relevance
“…In another study of older men, three total sets of knee extensor training per bout led to significant myofiber hypertrophy on a 3 days/wk program (19). Furthermore, our laboratory previously found that 4 sets of loading per bout induced robust myofiber hypertrophy in older men on a 3 days/wk training frequency (although growth remained impaired among the older women) (6). Based on these combined findings, the older adults in the present study may have realized greater myofiber growth by reducing loading volume even if frequency was maintained at 3 days/wk.…”
Section: Age Differences In Resistance Training-induced Myofiber Hypementioning
confidence: 92%
See 1 more Smart Citation
“…In another study of older men, three total sets of knee extensor training per bout led to significant myofiber hypertrophy on a 3 days/wk program (19). Furthermore, our laboratory previously found that 4 sets of loading per bout induced robust myofiber hypertrophy in older men on a 3 days/wk training frequency (although growth remained impaired among the older women) (6). Based on these combined findings, the older adults in the present study may have realized greater myofiber growth by reducing loading volume even if frequency was maintained at 3 days/wk.…”
Section: Age Differences In Resistance Training-induced Myofiber Hypementioning
confidence: 92%
“…All subject groups showed a typical compensatory shift in MHC isoform expression that is generally accepted to occur in response to both endurance (54) and resistance (1,6,20,60) training. There was a marked decrease in the number of histologically determined myofibers expressing exclusively MHC IIx in all groups, whereas the number of MHC IIa expressing myofibers significantly increased in all but elderly women.…”
Section: Strength Vs Hypertrophy; Non-muscle-mass Adaptationsmentioning
confidence: 93%
“…Despite its general effectiveness, the degree of RT-induced muscle hypertrophy varies across different age and gender groups Tracy et al, 1999;Welle et al, 1996). We and others have previously observed a blunted hypertrophic response in older females following long-term RT (Bamman et al, 2003;Ivey et al, 2000;Kosek et al, 2006). Although the underlying mechanism has not been well-defined, the divergent extent of hypertrophy in old females may occur in part from reduced myogenic aptitude (Gallegly et al, 2004;Leiter et al, 2011), which could conceivably impair the regenerative processes activated in response to mechanical loading.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, endurance (97,98,(104)(105)(106)(107)(108)(109)(110) exercise was shown to enhance the skeletal muscle oxidative capacity, resulting in greater endurance capacity (5,120) . Although the muscle regenerative capacity seems to decline at a more advanced age, the reduced satellite cell pool size (119) does not compromise the capacity for muscle hypertrophy to occur even at an advanced age (121)(122)(123) and resistance exercise training was shown to increase muscle fibre size (124)(125)(126)(127) .…”
Section: Long-term Interventionsmentioning
confidence: 99%